Política social e movimento social: projeto dos jesuítas na região de Perus/SP (1998 a 2008) experiência de protagonismo juvenil - Fritzen, Carlos (2014)
The present study aims to elucidate the elements which contribute to the discussion and reflection of social policy within the framework of neoliberal globalization considering that its positive and negative impacts have led to the segregation of impoverished sectors. Although with their social rights of citizens constitutionally recognized, as they are pushed to geographical and social peripheries, this group has been assisted by insufficient and fragmented social policies defined by the neoliberal system. Perversely, this system keeps them dependent and in this way, cannot effectively transforms the realities of misery and poverty nor generates the autonomy and leadership of the people, continually robbed of their rights, in the other extreme, growing accumulation of capital in the hands of a few and the difference in income distribution is accentuated. In this scenario, the proliferation of official discourses of "social inclusion ", non-governmental organizations promotes social projects with strategic focus on promoting political participation in various social movements for improvements in social policies directed at the population in a situation of economic and social vulnerability. From the theoretical research and the social bases of the jesuits, especially on social policies, there was a case study of the Social maintained by the jesuits in the outskirts of Turkeys - SP in the period 1998- 2008, which offered training activities integral to community - personal , civic , professional and community leaders. The results answer the initial hypothesis that social projects with this approach positively impact the lives of young people and their communities in the face of hegemonic neoliberal globalization and resulting fragmentation of social policies. In particular, this study highlights the importance of participation in the development of perception and critical awareness of the attendants about social phenomena and the ability of individual and collective political action in various contexts. Additionally shown are the limits, possibilities and challenges of a social project of this nature and indications for possible redirection of social action of the jesuits in the region